Fishing, trade, and local ecological knowledge of the marine gastropod, Cassis tuberosa – a target species of the international shell trade - Mota, Ellori Laise Silva; Alves, Rômulo Romeu da Nóbrega; Dias, Thelma Lúcia Pereira (Ethnobiology and Conservation, 2020)
Cassis tuberosa is one of the most exploited marine gastropods on the Brazilian coast, due to its aesthetic value. The lack of characterization of the species’ trade makes it difficult to establish effective monitoring strategies. This is the first survey to characterize the fishing and trade chain of C. tuberosa, and to record aspects of local fishermen’s traditional ecological knowledge of the species. C. tuberosa is caught while fishing for other target resources, such as fish, lobsters, and octopuses. The most popular use of the shell is for ornamental purposes, and the demand for this is enhanced by the intensive tourism. Knowledge of capture techniques and species usefulness is transmitted vertically in the community. The local ecological knowledge points to a population decline over time and attributes such decline to increased fishing. We hope the characterization provided in this study will contribute to the effective management of this species.